2022
DOI: 10.1016/j.jtumed.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Anterior abdominal wall metastasis following curative resection and chemoradiation of rectal cancer masquerading as a desmoid tumour: A clinical conundrum

Abstract: Desmoid tumour of the anterior abdominal wall (rectus sheath) commonly occurs in women post abdominal surgery. Metastasis from colorectal cancer to the anterior abdominal wall, on the other hand, is rare and produces a complex management dilemma. This Case study presents a 57-year-old woman who received a curative laparoscopic low anterior resection and adjuvant chemoradiation in 2013. Seven years later, she presented with an asymptomatic anterior abdominal wall lump. Clinically, the lump appeared to be a desm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Only limited numbers of case reports describe metastasis at the surgical drain site in patients with pancreatic, cervical, colorectal, thyroid, oesophageal and breast cancer 2. Clinical studies have shown that the incidence of abdominal wall recurrence is approximately 1% after laparotomy for colorectal cancer 3. This case reports the rare presentation of port-site recurrence post resection and adjuvant chemotherapy for a primary colorectal tumour at the ileocaecal valve.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Only limited numbers of case reports describe metastasis at the surgical drain site in patients with pancreatic, cervical, colorectal, thyroid, oesophageal and breast cancer 2. Clinical studies have shown that the incidence of abdominal wall recurrence is approximately 1% after laparotomy for colorectal cancer 3. This case reports the rare presentation of port-site recurrence post resection and adjuvant chemotherapy for a primary colorectal tumour at the ileocaecal valve.…”
Section: Discussionmentioning
confidence: 89%
“…When investigating an asymptomatic abdominal wall lesion, biopsy and histological assessment is required to differentiate between pathologies. This can help differentiate between other benign presentations such as hyperplastic granulation tissue, keloid scars and desmoid tumours 3. Hughes et al conducted a case series whereby 11 of 1603 patients developed recurrence at their abdominal incision after curative resection of large bowel cancer 11.…”
Section: Discussionmentioning
confidence: 99%
“… 2 According to the latest World Health Organization (WHO) classification of soft tissue and bone tumors, a DT is an intermediate-grade neoplasm characterized by an invasive growth pattern into surrounding normal structures and, rarely, metastasis. 3 , 4 DTs are relatively rare, accounting for less than 3% of soft tissue tumors. 3 The invasive nature of DTs is evident from the propensity of the tumor cells to invade and engulf surrounding normal structures.…”
Section: Introductionmentioning
confidence: 99%
“…[2] According to the latest World Health Organization classification of soft tissue and bone tumors, a DT is an intermediate-grade neoplasm characterized by an invasive growth pattern into the surrounding normal structures and, very rarely, metastasis. [3,4] The invasive nature of DTs is evidenced by the propensity of tumor cells to invade and engulf surrounding normal structures, which poses an imminent danger when they grow adjacent to major blood vessels and other vital organs. [5,6] However, the pathogenesis of DTs remains unclear.…”
Section: Introductionmentioning
confidence: 99%